Molecular Docking Senyawa pada Buah Mengkudu (Morinda Citrifolia L.) terhadap Reseptor PDGFR-a sebagai Kandidat Antikanker Paru-Paru - Ma'ruf, Hanif Sabawi; Ramadhan, Muhammad Arvito; Syafriadi, Riko; Suryani , Okta (LP4M STIKes Karsa Husada Garut, 2025)
Introduction: The PDGFR-α (platelet-derived growth factor receptor alpha) receptor is one of the protein receptors implicated in the development of lung cancer by regulating proliferation, angiogenesis, and migration of cancer cells. The utilization of synthetic drugs in the treatment of cancer frequently results in the targeting of normal cells, which can lead to adverse effects in patients. Consequently, there is an imperative to engineer anticancer compounds derived from natural ingredients that exhibit a reduced incidence of adverse effects in comparison to synthetic drugs. In this study, the compounds present in noni fruit were utilized. The following section delineates the methods employed in this study. This study was conducted using a molecular docking method to identify the lowest docking score between the four most abundant compounds found in noni fruit and Gemcitabin, a positive control, against the PDGFR-α receptor. Method: This study was conducted using a molecular docking method, with the lowest docking score between the four most abundant compounds contained in noni fruit and Gemcitabin, a positive control, against the PDGFR-α receptor being of particular interest. Result: Subsequent to molecular docking, the compound demonstrating the optimal interaction among its counterparts is Nordamnacanthal, exhibiting a docking score of -6.49. This is followed by Morindone, α-Pinene, Gemcitabine, and L-Scopoletin, which demonstrate docking scores of -5.01, -4.83, -4.77, and -4.66, respectively. Conclusion: Nordamnacanthal compound exhibits a lower docking score in comparison to gemcitabine, a synthetic drug that is currently employed in the treatment of lung cancer. This finding suggests that Nordamnacanthal may be a promising candidate for anti-lung cancer drugs derived from natural compounds.